Increased sugar intake as a form of compensatory hyperphagia in patients with type 2 diabetes under dapagliflozin treatment. (January 2018) - Horie, Ichiro; Abiru, Norio; Hongo, Ryoko; Nakamura, Takeshi; Ito, Ayako; Haraguchi, Ai; Natsuda, Shoko; Sagara, Ikuko; Ando, Takao; Kawakami, Atsushi
Highlights: Compensatory hyperphagia caused by SGLT2 inhibitors is known in animal models. Compensatory hyperphagia was studied by a dietary questionnaire in human. Our results suggest dapagliflozin treatment increased intake of sucrose. The increased sugar intake may contribute to compensatory hyperphagia. Abstract: Aims: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) cause substantially less weight loss than would be expected based on their caloric deficits, probably due to enhanced appetite regulation known as "compensatory hyperphagia, " which occurs to offset the negative energy balance caused by increased glycosuria. We examined whether any specific nutrients contributed to the compensatory hyperphagia in diabetic patients taking SGLT2i. Methods: Sixteen patients with type 2 diabetes were newly administered dapagliflozin 5 mg daily as the experimental SGLT2i group. Sixteen age-, sex- and BMI-matched type 2 diabetes patients not receiving dapagliflozin served as controls. A brief-type self-administered diet history questionnaire (BDHQ) was undertaken just before and 3 months after study initiation to evaluate changes of energy and nutrient intakes in each group. Results: At 3 months, daily intakes of total calories and the proportions of the three major nutrients were not significantly increased in either group. However, daily sucrose intake was significantly increased after treatment versus the baseline value in the SGLT2i group (p = .003), but not in controls. The calculated intakes of all other nutrients were not significantly changed in either group. Conclusions: Dapagliflozin treatment specifically increased sucrose intake, which might be an ideal target for nutritional approaches to attenuate compensatory hyperphagia.